Motivasi Dalam Komunikasi Persuasif Untuk Meningkatkan Kinerja Bunda pengharapan Hospital - Poetri E Suradinata; Imelda C Laode; Vinsenco R Serano; Apolus Betaubun; Hairulla Hairulla (Musamus Journal of Public Administration, 2019)
The purpose of this study is to find out the provision of motivation in persuasive communication in order to improve the performance of the employees of Bunda Pengharapan Hospital in Merauke Regency, In this study researcher interviewed 10 people as research informants. Data analysis used descriptive qualitative method while this study used three stages, namely data presentation, data reduction and conclusion. From the results of this study, the researchers found that there was a work motivation that the leader did to the employees of BundaPengharapan Hospital so that the results of the employee's performance were good enough to carry out work duties every day. However, in the motivational indicator, it isnecessary to maintain more support or appreciation for employee work performance so as to further encourage employees to further improve or maintain their work performance in the Hospital.